Penerapan Pembelajaran Partisipatif dalam Edukasi Pemilahan Sampah untuk Mendukung Pembangunan Berkelanjutan di SDN 2 Bresela - Ni Ketut Budiningsih; Amrita Nugraheni Saraswaty; I Gusti Agung Ayu Apsari Anandari; I Wayan Priyana Agus Sudharma (Pusat Riset dan Inovasi Nasional, 2025)
Bresela Village, Gianyar, Bali has had a TPS3R facility since 2022, however household waste sorting remains suboptimal. Sustainable development requires environmental awareness from an early age, making environmental education in elementary schools strategic. This community service activity aimed to increase students' environmental knowledge and encourage behavioral change toward a cleaner and more sustainable life. The activity was conducted at SDN 2 Bresela on July 25, 2025 with 34 students from grades 4, 5, and 6 using a participatory approach and active learning methods through three stages: environmental education counseling, waste sorting simulation, and educational games. Results showed 100% attendance with an average knowledge score increase from 62.9 to 79 points (16.1% increase). A total of 94.12% of participants experienced increased knowledge scores and 82.35% of students achieved scores ≥70. Students demonstrated the ability to correctly sort organic and inorganic waste along with the emergence of new habits such as independently cleaning classrooms and using waste bins according to categories. This activity proves that environmental education through an experiential learning approach effectively increases knowledge and shapes pro-environmental behavior in elementary school students.